Distribution of HLA‐G extended haplotypes and one HLA‐E polymorphism in a large‐scale study of mother–child dyads with and without severe preeclampsia and eclampsia. (6th September 2016) - Nilsson, L. L.; Djurisic, S.; Andersen, A.‐M. N.; Melbye, M.; Bjerre, D.; Ferrero‐Miliani, L.; Hackmon, R.; Geraghty, D. E.; Hviid, T. V. F.
Abstract: The etiological pathways and pathogenesis of preeclampsia have rendered difficult to disentangle. Accumulating evidence points toward a maladapted maternal immune system, which may involve aberrant placental expression of immunomodulatory human leukocyte antigen (HLA) class Ib molecules during pregnancy. Several studies have shown aberrant or reduced expression of HLA‐G in the placenta and in maternal blood in cases of preeclampsia compared with controls. Unlike classical HLA class Ia loci, the nonclassical HLA‐G has limited polymorphic variants. Most nucleotide variations are clustered in the 5′‐upstream regulatory region (5′URR) and 3′‐untranslated regulatory region (3′UTR) of HLA‐G and reflect a stringent expressional control. Based on genotyping and full gene sequencing of HLA‐G in a large number of cases and controls ( n > 900), the present study, which to our knowledge is the largest and most comprehensive performed, investigated the association between the HLA‐G 14‐bp ins/del (rs66554220) and HLA‐E polymorphisms in mother and newborn dyads from pregnancies complicated by severe preeclampsia/eclampsia and from uncomplicated pregnancies. Furthermore, results from extended HLA‐G haplotyping in the newborns are presented in order to assess whether a combined contribution of nucleotide variations spanning the 5′URR, coding region, and 3′UTR of HLA‐G describes the genetic association with severe preeclampsia more closely. In contrast to earlier findings, the HLA‐G 14‐bp ins/del polymorphism was not associated with severe preeclampsia. Furthermore, the polymorphism (rs1264457) defining the two nonsynonymous HLA‐E alleles, HLA‐E*01:01:xx:xx and HLA‐E*01:03:xx:xx, were not associated with severe preeclampsia. Finally, no specific HLA‐G haplotypes were significantly associated with increased risk of developing severe preeclampsia/eclampsia.